Edutok: A Conceptual Study of Tik-Tok as a Media in Teaching and Learning English - Ekorini, Puput Zuli; Rosiana, Caltira (International Journal on Advanced Science, Education, and Religion, 2024)
This study is a qualitative investigation aimed at exploring the role of the TikTok platform in English language learning. Employing a conceptual-empirical approach, the research utilises data gathered from observations conducted by the researchers. This empirical data serves to examine a phenomenon independently of existing theoretical frameworks. The analysis of both conceptual and empirical data reveals that the TikTok platform functions as an effective learning medium, facilitating students' enhancement of their English skills across listening, speaking, reading, writing, and supplementary competencies such as grammar. Furthermore, it was discovered that the integration of TikTok into the learning process affords students opportunities to engage with experiences and knowledge beyond the confines of the classroom. Consequently, students develop a positive outlook, bolstered by increased self-confidence in their English learning journey.